Illegal Downloading, Ethical Concern, and Illegal Behavior - Robertson, Kirsten; McNeill, Lisa; Green, James; Roberts, Claire (2012)
Illegally downloading music through peer-to-peer networks has persisted in spite of legal action to deter the behavior. This study examines the individual characteristics of downloaders which could explain why they are not dissuaded by messages that downloading is illegal. We compared downloaders to non-downloaders and examined whether downloaders were characterized by less ethical concern, engagement in illegal behavior, and a propensity toward stealing a CD from a music store under varying levels of risk. We also examined whether downloading or individual characteristics of downloaders were similar for men and women. Findings revealed downloading was prevalent (74.5% of the student sample downloaded), men and women were equally likely to download and the factors characterizing downloading were similar for men and women. The comparison between downloaders and non-downloaders revealed downloaders were less concerned with the law, demonstrated by less ethical concern and engagement in other illegal behaviors. Downloaders were also more likely to indicate that they would steal a CD when there was no risk of being caught. Given these results, messages regarding illegality are unlikely to perturb downloaders and alternative recommendations are offered for targeting illegal downloading.
Keywords: Students’ illegal downloading; Stealing a CD and illegal downloading; music piracy; Risky behavior and illegal downloading